Analysis of Runoff Aggregation Structures with Different Flow Direction Methods under the Framework of Power Law Distribution - Kok K.; Mohd Sidek L.; Jung K.; Kim J.C. (Springer Netherlands, 2023)
Dispersions; Maximum likelihood estimation; Parameter estimation; Aggregation structure; Flow accumulation; Flow direction; Multiple flows; Power law distribution; Runoff; digital elevation model; flow pattern; parameter estimation; power law distribution; river basin; river flow; runoff; size distribution; Ganges Basin; Platanista